2017
DOI: 10.1097/inf.0000000000001720
|View full text |Cite
|
Sign up to set email alerts
|

Magnusiomyces capitatus Peritonitis in a Child With Acute Lymphocytic Leukemia as a Breakthrough Infection During Caspofungin Therapy

Abstract: Magnusiomyces capitatus is an emerging opportunistic fungal pathogen particularly in immunocompromised patients. We report a case of a M. capitatus peritonitis in child with acute lymphocytic leukemia as a breakthrough infection during caspofungin therapy. The possibility of breakthrough infections caused by M. capitatus must be taken into consideration, particularly in immunosupressed patients being treated for systemic fungal infections by caspofungin. Although there are no defined breakpoints for susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…To our knowledge, this is the first reported case of S. capitata peritonitis with a fatal outcome in a patient without neutropenia or associated malignancy. Bariş et al reported a case of peritonitis due to S. capitat a in a child with acute lymphocytic leukemia during caspofungin therapy; the patient’s condition was improved after antifungal treatment adjustment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first reported case of S. capitata peritonitis with a fatal outcome in a patient without neutropenia or associated malignancy. Bariş et al reported a case of peritonitis due to S. capitat a in a child with acute lymphocytic leukemia during caspofungin therapy; the patient’s condition was improved after antifungal treatment adjustment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…are urease negativity of Saprochaete spp. and its ability to grow on Sabouraud dextrose agar with cycloheximide [ 3 , 10 ]. Microscopically, Saprochaete spp.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, precise and prompt diagnosis, as well as treatment, emerge as pivotal challenges [27]. As susceptibility breakpoints have not yet been established for M. capitatus [28], we employed breakpoints recommended by the CLSI M27-A3 document for other related yeast species to overcome this limitation. Based on the in vitro susceptibility results, the highest MICs were observed for fluconazole and caspofungin.…”
Section: Mortalitymentioning
confidence: 99%
“…In this review, 82% (61/74) of the publications reported peritoneal dialysis-related peritonitis. When data were available, other risk factors for peritonitis were underlying neoplasia [118], gastric and duodenal ulcer perforation [119], recent digestive surgery [120][121][122][123][124], severe immunosuppression [125,126], and pancreatitis [127]. In some cases, infection of the peritoneum, as well as other unusual infection sites including the biliary tract (9 publications), gastric tract (12 publications), and spleen (19 publications), may also be a secondary condition to the haematogenous dissemination of yeasts [128].…”
Section: Digestive Systemmentioning
confidence: 99%